A novel anti-cancer effect of genistein: reversal of epithelial mesenchymal transition in prostate cancer cells - Zhang Lin-lin; Li Lei; Wu Da-peng; Fan Jin-hai; Li Xiang; Wu Kai-jie; Wang Xin-yang; He Da-lin (Acta Pharmacologica Sinica, 2016)
Aim: The aim of the present study was to investigate whether low dose genistein affects the invasion and epithelial mesenchymal transition (EMT) of prostate cancer (PCa) cells. Methods: Human PCa cell lines, IA8-ARCaP and LNCaP/HIF-1a, were used in this study. The cell lines were found to process EMT in our previous study. The PCa cells were treated with increasing concentrations, from 0.1 to 75μmol/L. Proliferation was assessed with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. EMT was proven by cell morphological transition and the expression changes of EMT-related markers, which were confirmed by RT-PCR, Western blotting, and indirect immunofluorescence labeling. Transwell invasion assay was used to analyze the invasive potency. Results: The addition of genistein to the medium reduced the IA8-ARCaP and LNCaP/HIF-1a viable cell number in a dose-dependent manner (with increasing concentrations from 15 to 75 μmol/L). Less than 15 μmol/L genistein was selected as the low dose concentration, which did not affect cell proliferation. The treatment of cells with low-dose genistein induced the reversal of EMT, which was confirmed by cell morphological transition and the expression changes of EMT-related markers. The reversal of EMT in the PCa cells by low-dose genistein was in a dose-dependent manner. Moreover, low-dose genistein effectively inhibited invasion of the PCa cells in vitro. Conclusion: These results showed that treatment with low-dose genistein may be a potential strategy for the suppression of invasive growth through the reversal of EMT in cancer cells, which justifies the potential use of soybean foods as a practical chemopreventive approach for patients with PCa.